2020
DOI: 10.1093/geroni/igaa051
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Substance Use Treatment Completion Among Older Adults

Abstract: Background and Objectives Racial disparities in substance use among young adults has been well-documented in the substance use literature, but little attention has been paid to older adults. While being an older adult is positively associated with substance use treatment completion, racial disparities in treatment completion have yet to be examined. The purpose of this study was to determine to what extent racial disparities exist in substance use treatment completion among older adults (65 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…There also exist disparities in completion of substance use treatment programs. Suntai et al found that, among older adults, Black older adults were 37% less likely to complete a substance use treatment program than Whites, while Hispanic older adults were 26% more likely to complete a substance use treatment than Whites [ 84 ]. These results are similar to the results shown in studies of younger adults, suggesting that racial disparities must be addressed in substance use treatment across ages.…”
Section: Resultsmentioning
confidence: 99%
“…There also exist disparities in completion of substance use treatment programs. Suntai et al found that, among older adults, Black older adults were 37% less likely to complete a substance use treatment program than Whites, while Hispanic older adults were 26% more likely to complete a substance use treatment than Whites [ 84 ]. These results are similar to the results shown in studies of younger adults, suggesting that racial disparities must be addressed in substance use treatment across ages.…”
Section: Resultsmentioning
confidence: 99%
“…The authors (Whitehead et al, 2014 ) observed that older Black participants were two times more likely to use crack in the past 6 months as compared to their younger counterparts. In another study by Suntai et al ( 2020 ), older Black adults were less likely to complete a substance use treatment program than their White counterparts. Lack of substance use treatment may be a factor associated with higher illicit drug use and the combination of both prescription drug misuse and illicit drug use, as observed in this research.…”
Section: Discussionmentioning
confidence: 96%
“…Racial and ethnic disparities continue to be a factor associated with different health outcomes or health behaviors in the United States among various age groups (Chen et al, 2016 ; Churchwell et al, 2020 ; Fiscella & Sanders, 2016 ; Gandhi et al, 2020 ; Gollust et al, 2018 ; Hammonds & Reverby, 2019 ; Lebrun & LaVeist, 2011 ; Manuel, 2018 ; Norton et al, 2016 ; Suntai et al, 2020 ). Racial and ethnic disparities also exist in other public health challenges like illicit drug use and prescription drug misuse.…”
Section: Introductionmentioning
confidence: 99%
“…Among Black patients, ischemic stroke was significantly higher among PWUD. Previous work has acknowledged the systemic and institutional disadvantages faced by women and racial/ethnic minorities when receiving care for IE and for substance use disorders in general [ 15 , 38 ]. The recommendations of previous authors and the American Association for Thoracic Surgery, including the need to connect PWUD to addiction medicine services, with special attention to vulnerable demographic populations, are especially relevant [ 18 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%